2015
DOI: 10.1097/ccm.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

β1-Adrenergic Inhibition Improves Cardiac and Vascular Function in Experimental Septic Shock*

Abstract: Adjunction of selective β1-blockade to standard septic shock management enhances intrinsic cardiac contractility and vascular responsiveness to catecholamines. These protective cardiovascular effects are likely predominantly attributed to the anti-inflammatory effect of esmolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
60
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 29 publications
10
60
1
1
Order By: Relevance
“…However, they failed to provide any supporting data, and one may argue that anti-inflammatory effects would unlikely have occurred this swiftly, i.e., after only four hours of treatment (12)(13)(14)(15).…”
Section: Study Design and Findingsmentioning
confidence: 99%
“…However, they failed to provide any supporting data, and one may argue that anti-inflammatory effects would unlikely have occurred this swiftly, i.e., after only four hours of treatment (12)(13)(14)(15).…”
Section: Study Design and Findingsmentioning
confidence: 99%
“…Excessive adrenergic stimulation is harmful to the heart (3). In animal studies, esmolol, a selective beta-1-adrenergic blocker, improves cardiac contractility, stroke volume (SV) and vascular responsiveness to norepinephrine (4)(5)(6). In patients with septic shock who were initially stabilized, Morelli et al showed that esmolol infusion reduced heart rate, increased SV and reduced norepinephrine requirements (7).…”
mentioning
confidence: 99%
“…Analysis of a human database identified the upregulation of CAMP (p = 0.032) and TNFSF10 (p = 0.001) genes in septic patients compared with healthy controls [13]. In another animal model, esmolol decreased NFKB activation, increased Akt and endothelial nitric oxide synthase phosphorylation, while lowering inducible nitric oxide synthase expression in cardiac and vessel tissues [11]. Esmolol also improves LPS-induced ventricular dysfunction [14].…”
mentioning
confidence: 99%
“…A recent systematic review of beta-blockade in sepsis suggests some benefit, but there is still work to do because of the lack of large RCTs-most studies are small and uncontrolled case series/cohorts [7]. In addition to its beneficial effects on cardiac dynamics, beta-blockade may exert beneficial pleiotropic effects including blunting the inflammatory response, metabolic changes, and sepsis-associated coagulopathy [10][11][12][13][14]. Furthermore, beta-blockade may increase microcirculatory/small vessel blood flow in a small cohort (n = 25) of patients with sepsis [10].…”
mentioning
confidence: 99%